1972
DOI: 10.1172/jci107115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age, sex, and site on the cellularity of the adipose tissue in mice and rats rendered obese by a high-fat diet

Abstract: A B S T R A C T Cell size and number of parametrial fat pads were determined in Swiss mice made obese by means of a high-fat diet (40% lard w/w) given ad lib.This diet and a control were introduced to two groups of mothers during gestation and lactation, and sucklings were given the same diets as their mothers at weaning and throughout life.2-wk old mice suckled by mothers fed a high-fat diet have fatter parametrial pads. This difference is due solely to an increase in fat cell size. After weaning, until the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
137
0
9

Year Published

1978
1978
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 302 publications
(152 citation statements)
references
References 20 publications
6
137
0
9
Order By: Relevance
“…This overweight could be attributed to an increase in adipose mass as shown by the weight of the three fat pad depots. A marked sensitivity to high-fat diet has already been found in the parametrial adipose tissue of these mice : the fat cells of that fat pad showed hypertrophy and hyperplasia (Lemonnier, 1972). This type of obesity could not be related to hyperphagia : the food intake was reduced in weight, but expressed in terms of calories, it was slightly higher.…”
Section: Methodsmentioning
confidence: 77%
See 3 more Smart Citations
“…This overweight could be attributed to an increase in adipose mass as shown by the weight of the three fat pad depots. A marked sensitivity to high-fat diet has already been found in the parametrial adipose tissue of these mice : the fat cells of that fat pad showed hypertrophy and hyperplasia (Lemonnier, 1972). This type of obesity could not be related to hyperphagia : the food intake was reduced in weight, but expressed in terms of calories, it was slightly higher.…”
Section: Methodsmentioning
confidence: 77%
“…These cells did not approach their maximal size (Lemonnier, 1972) ; only a slight increase in their number was observed. Progesterone therefore had the same effect on the cellularity of the control and the obese mice.…”
Section: Methodsmentioning
confidence: 85%
See 2 more Smart Citations
“…An early report by Lemonnier (1972) concluded that the cell number in the perirenal and parametrial fat depots in adult rats could be affected by dietary manipulations. It was not clear, however, if the hyperplasia reported was due to the appearance of new cells or to the filling of preadipocytes.…”
Section: Nutritional Influencesmentioning
confidence: 99%